Comparison of 10% vs. 30% Velocity Loss during Squat Training with Low Loads on Strength and Sport-Specific Performance in Young Soccer Players - Andrés Rojas-Jaramillo; Gustavo León-Sánchez; África Calvo-Lluch; Juan José González-Badillo; David Rodríguez-Rosell (MDPI AG, 2024)
The aim of this study was to compare the effects of two velocity-based resistance training (RT) programs using moderate loads (45-60% 1RM) but different magnitudes of velocity loss (VL) limits (10% vs. 30%) on the changes in physical performance in young soccer players. Twenty young soccer players were randomly allocated into two groups: VL10% (n = 10) and VL30% (n = 10). All participants were assessed before and after the 8-week RT program (twice a week) involving the following tests: 20 m running sprint (T20), countermovement jump (CMJ), kicking a ball (KB), and progressive loading test in the full squat (SQ) exercise. The RT program was conducted using only the SQ exercise and movement velocity was monitored in all repetitions. Significant 'time × group' interaction (p < 0.05) was observed for sprint performance, KB and 1RM in the SQ exercise in favor of VL10%. No significant changes between groups at post-test were observed. The VL10% resulted in significant (p < 0.05-0.001) intra-group changes in all variables analyzed, except for KB, whereas VL30% only showed significant (p < 0.05) performance increments in a sprint test and 1RM in the SQ exercise. The percentage of change and the intra-group's effect size were of greater magnitude for VL10% in all variables analyzed compared to VL30%. In conclusion, our results suggest that, for non-trained young soccer players, squat training with low to moderate relative loads and 10%VL is sufficient to elicit significant increases in muscle strength and sport-specific actions compared to 30%VL in the set.